1991
DOI: 10.1113/jphysiol.1991.sp018546
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological effects of calcitonin gene‐related peptide in bull‐frog and guinea‐pig atrial myocytes.

Abstract: SUMMARY1. Electrophysiological effects of calcitonin gene-related peptide (CGRP) on action potentials and corresponding transmembrane currents in single myocytes from bull-frog and guinea-pig atria were studied using a whole-cell voltage-clamp method.2. CGRP at relatively low concentrations increased the height of the action potential plateau in a dose-dependent manner in both bull-frog and guinea-pig myocytes. In addition, in bull-frog cells CGRP accelerated the early phase of repolarization, thus shortening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…These effects are believed to be due to opening of KATP channels or to direct interactions with guanine nucleotide binding proteins coupled to ion channels or to exocytotic machinery (13,27). Similarly, calcitonin-gene-related peptide (CGRP), which shares 46% sequence homology with amylin and modulates K and Ca currents in muscle and nerve (28)(29)(30)(31), reduces insulin secretion from both single rat (8 cells and islets (32,33). Although it is possible that local (3cell effects of amylin are mediated through low-affinity CGRP receptors (34), both amylin secretion from the , cell and its link to type II diabetes make it unique among peptide and hormone modulators of the l3 cell (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…These effects are believed to be due to opening of KATP channels or to direct interactions with guanine nucleotide binding proteins coupled to ion channels or to exocytotic machinery (13,27). Similarly, calcitonin-gene-related peptide (CGRP), which shares 46% sequence homology with amylin and modulates K and Ca currents in muscle and nerve (28)(29)(30)(31), reduces insulin secretion from both single rat (8 cells and islets (32,33). Although it is possible that local (3cell effects of amylin are mediated through low-affinity CGRP receptors (34), both amylin secretion from the , cell and its link to type II diabetes make it unique among peptide and hormone modulators of the l3 cell (35,36).…”
Section: Resultsmentioning
confidence: 99%
“…To explore the ionic mechanism(s) of these CNP effects on the action potential, voltage clamp measurements of I Ca were made as described previously (50). The effects of CNP were first measured on basal (unstimulated) I Ca .…”
Section: Effects Of Cnp On I Camentioning
confidence: 99%
“…This corresponds well with the study of Bell and McDermott [6] who have demonstrated that the positive inotropic effect of CGRP in rat ventricular myocytes is not antagonized by the selective L-type Ca 2+ channel antagonists, diltiazem or verapamil. On the other hand, in preparations such as guinea-pig atrial myocytes, CGRP stimulates cAMP production and I Ca,L [16,23,24]. Increased cAMP levels in the presence of CGRP have been reported also in cultured neonatal rat myocardial cells [22] and in rat atria [15,29] but not in ventricles [15].…”
Section: Discussionmentioning
confidence: 93%
“…With regard to the inotropic effects conflicting results have been reported depending on the animal species and tissue studied. The positive inotropic effect in guinea-pig atrial myocytes has been attributed to the stimulation of Ca 2+ currents and adenosine 3′,5′-cyclic monophosphate (cAMP) production [16,23,24]. In rat ventricular cells a positive inotropic effect is also found, although it is insensitive to selective blockers of L-type Ca 2+ channels as well as to a cAMP antagonist [4,5,6].…”
Section: Introductionmentioning
confidence: 96%